Pengaruh Media Sosial Dan Word Of Mouth Melalui Brand Awareness Sebagai Variabel Mediasi Terhadap Keputusan Pembelian Djovalyn - Andriani, Diah Fitri (PERFORMA, 2022)
The purpose of this research is to find out the effect of social media and word of mouth on brand awareness and purchase decision of Djovalyn. This research is quantitative research with population of this research that is obtain from Djovalyn consumers in February 2020 to January 2021 as many as 44 people. Data collected technique uses questionnaire and data is analyze by using Smart PLS (SEM). The result of this research shows that social media variable has significant effect on brand awareness which means attractive social media can increase brand awareness. However, the different result that is found in social media variable does not effect significant of purchase decision. This thing is due to some communities are still doubtful of social media such as instagram for shopping compared with ecommerce. Word of mouth variable has significant effect on brand awareness and purchase decision. This thing means the stronger existence of a brand in consumer's mind, therefore the higher the consumers to consider or talk about certain brand.